2021
DOI: 10.3906/bot-2104-21
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis reveals weak population structure in invasive Trianthema portulacastrum L. at Fayoum depression, Egypt

Abstract: Trianthema portulacastrum L. (Aizoaceae) is a common weed associated with cultivated crops. It is an exotic weed that originated in South Africa and is spreading all over the world. Thirty-five accessions were collected from six populations at Fayoum depression (FD), Egypt. Molecular analyses of Start Codon Targeted (SCoT) markers were performed to identify genotypic variation among collected populations. The effectiveness of employing SCoT markers was demonstrated by the high percentage of polymorphisms. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In Egypt, Shaltout et al [ 27 ] studied the distributional behavior and the growth performance of T. portulacastrum in the Nile Delta, indicating that its spread might lead to a severe ecological disaster. Recently, Ellmouni et al [ 28 ] reported the significant variations between T. portulacastrum genotypes within the same population, along with the existence of sexual and clonal reproduction in the Fayoum Depression (FD), implying that local adaptation and phenotypic plasticity can help species invasion.…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, Shaltout et al [ 27 ] studied the distributional behavior and the growth performance of T. portulacastrum in the Nile Delta, indicating that its spread might lead to a severe ecological disaster. Recently, Ellmouni et al [ 28 ] reported the significant variations between T. portulacastrum genotypes within the same population, along with the existence of sexual and clonal reproduction in the Fayoum Depression (FD), implying that local adaptation and phenotypic plasticity can help species invasion.…”
Section: Introductionmentioning
confidence: 99%